2016
DOI: 10.1155/2016/1841287
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Based User-Centered Learning Environment for Adult Absolute Illiterates

Abstract: Education plays a vital role in the success of any community. Countries with increased literacy rate have improved their status on the world map. In recent years, the use of e-learning methodologies has been significant. However, majority of the previous methodologies are focused on the formal education or toddlers. The technoliteracy solutions for children are not suitable for adults and those designed specifically for adults are text dominant and require the users of these applications to be functional liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Nevertheless, the majority of the studies that were found in the literature focused mainly on determining the methods and approaches with regard to the content and technical presentation [1]. Even though the study of 'acceptance' has been tested and evaluated in many situations, it still needs to be refined owing to different technologies (including m-Learning) and the need for different approaches within different contexts or environments [41].…”
Section: Adult Learning Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the majority of the studies that were found in the literature focused mainly on determining the methods and approaches with regard to the content and technical presentation [1]. Even though the study of 'acceptance' has been tested and evaluated in many situations, it still needs to be refined owing to different technologies (including m-Learning) and the need for different approaches within different contexts or environments [41].…”
Section: Adult Learning Principlesmentioning
confidence: 99%
“…Teaching and learning strategies have also presented opportunities to adult learners seeking information in various ways regarding their preferences and learning styles. These can be used efficiently for some activities such as question and answer sessions, cooperation, game-based learning, decisionmaking, and problem-solving in specific learning situations [1], [23], [91].…”
Section: E Instructional Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, educators have turned their attention to 3D virtual environments because they have great potential to simulate near-real-life experiences in a cost-effective way that makes them suitable for learning from traditional binary applications. (Inayat ur-Rehman & Azra Shamim, 2016) Technology for adults with low levels of literacy has facilitated effective communication with mobile application, and interaction with mobile technology through touch screens is a simple and easy mechanism for adults with limited literacy skills. Continuous learning is essential for literacy-free people, adult literacy programs and associated program applications play an effective role in raising literacy levels and supporting their day-to-day tasks in education.…”
Section: Introductionmentioning
confidence: 99%